Removal of Pb (II) Ions from Aqueous Solutions by Cladophora rivularis (Linnaeus) Hoek - Naser Jafari; Zoreh Senobari (The Scientific World Journal)
Biosorption of Pb(II) using Cladophora rivularis was examined as a function of initial pH heavy metal concentration and temperature. The optimum pH value for the biosorption of lead was 4.0. The adsorption equilibriums were well described by Langmuir and Freundlich isotherm models and it was implied by the results that the C. rivularis biomass is suitable for the development of efficient biosorbent in order to remove Pb(II) from wastewater and to recover it. The high values of correlation coefficient (𝑅2=0.984) demonstrate equilibrium data concerning algal biomass, which is well fitted in Freundlich isotherms model equations. The dimensionless parameter RL is found in the range of 0.0639 to 0.1925 (0<𝑅𝐿<1), which confirms the favorable biosorption process. Fourier transform infra-red (FTIR) spectroscopy of C. rivularis was used to reveal the main function groups of biosorption, which were hydroxyl, amine groups, C–H stretching vibrations of –CH3 and –CH2, and complexation with functional groups. All these results suggest that C. rivularis can be used effectively for removal of Pb(II).